Fenomena Penggunaan Generative AI dalam Perilaku Pencarian Informasi Praktisi Teknologi - Hibatulwafi, Fathe; Laksmi, Laksmi (Media Pustakawan, 2024)
The emergence of generative AI technology which has provided new experiences for technology practitioners in searching for information to obtain professional information needs and complete their tasks, needs to be studied further as an effort to anticipate various impacts and potentials that may occur. Therefore, research is needed that identifies the use of generative AI technology in the information behavior patterns of technology practitioners at the start-up company PT XYZ. This research used qualitative with phenomenological approach. Based on the experiences of the three informants when using generative AI to search for information, the informants had different needs, but the informants had positive experiences in using generative AI to search for information, so that it could be an alternative solution to the needs and problems they experienced. Informants have varied experiences in searching for information, and in some contexts there are even experiences of using similar strategies. Several strategies from the informants' search experiences consisted of using simple prompts, using prompts that were supported by additional context, and using prompts that contained scenarios and narratives. The information seeking behavior pattern of technology practitioners who uses generative AI in PT XYZ were identified as very varied based on their task and job functions, both in terms of needs and the search strategies they used.